Zmiany wybranych wskaźników zdrowia kobiet w wieku 60-74 lata w dwuletnim cyklu treningu zdrowotnego = Changes in selected health indicators for women aged 60-74 years in the two-year cycle of health training - Krzysztof Prusik; Zbiegniew Ossowski; Jakub Kortas; Monika Wiech; Łukasz Bielawa; Seweryna Konieczna; Katarzyna Prusik (Kazimierz Wielki University, 2016)
Prusik, Krzysztof, Ossowski, Zbigniew, Kortas, Jakub, Wiech, Monika, Bielawa, Łukasz, Konieczna, Seweryna, Prusik, Katarzyna. Zmiany wybranych wskaźników zdrowia kobiet w wieku 60-74 lata w dwuletnim cyklu treningu zdrowotnego = Changes in selected health indicators for women aged 60-74 years in the two-year cycle of health training. Journal of Education, Health and Sport. 2016;6(3):72-80. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47555 http://ojs.ukw.edu.pl/index.php/johs/article/view/3424 https://pbn.nauka.gov.pl/works/720099   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016.     Zmiany wybranych wskaźników zdrowia kobiet w wieku 60-74 lata w dwuletnim cyklu treningu zdrowotnego   Changes in selected health indicators for women aged 60-74 years in the two-year cycle of health training   Krzysztof Prusik1, Zbigniew Ossowski1, Jakub Kortas1, Monika Wiech1, Łukasz Bielawa1, Seweryna Konieczna2, Katarzyna Prusik1   1Academy of Physical Education and Sport in Gdansk 2Medical University of Gdansk   Keywords: Nordic Walking, health training. Słowa kluczowe: Nordic Walking, trening zdrowotny.   Abstract Modern vision of health promotion, which is striving to maintain physical, mental and intellectual lifelong, is a current problem for every man and especially the elderly, in whom is observed pressure changes involution. The aim of the study is to determine changes in selected health indicators for women aged 60-74 years in the two-year cycle of health training in the form of Nordic Walking. Obtained empirical data describing: physical fitness tests ("Eurofit adult", "Fullerton Fitness Test" march 2000m), efficiency (PWC130), construction of the somatic (body weight, BMI, FAT%, FAT mass, FFM, TBW). The study group (experimental) represents 15 women aged 60 to 74 years, participating in the two full annual macrocycles (2011-13r.) In health training in the form of Nordic Walking. The control group produces 15 women of the same age is not participating in any form of physical activity. The results of the research are entitled to the following statements: 1. health training in the form of Nordic Walking is an effective stimulus changes in health indicators for women aged 60-74 years by 30% in terms of flexibility of the trunk 2. health training is a factor that may slow down the long term involution changes in selected health indicators for women aged 60-75 years by up to 48% in terms of strength and 247% in terms of flexibility shoulders.